The interplay between cultural models and metaphor understanding: a cross-cultural cognitive perspective - Jun Zou; Carol Fuller; Linyao Wang (Frontiers in Psychology, 2025)
In cross-cultural communication, accurate metaphor comprehension enhances mutual understanding and facilitates effective cooperation among individuals from diverse cultural backgrounds. This paper adopts a cross-cultural cognitive perspective and employs grounded theory as the methodological framework to analyze how cultural models influence metaphor understanding. Through a coding analysis of 148 domestic and international texts, the study constructs a four-element model comprising thinking patterns, cognitive frameworks, language communication, and social consensus. Thinking patterns shape cognitive frameworks, which are articulated and transmitted through language communication, ultimately contributing to the formation of social consensus within cultural groups. These four interrelated elements work together to support deeper and more accurate metaphor comprehension in intercultural contexts. By integrating theory with empirical analysis, this study offers a novel conceptual framework for future research on metaphor in cross-cultural communication.